Case report: Visual acuity loss as a warning sign of ocular syphilis: A retrospective analysis of 17 cases - Xu, Yating; Li, Jingjing; Xu, Yuxuan; Xia, Wei; Mo, Xingfan; Feng, Mingzhi; He, Fanghua; Li, Shanshan; Du, Fangzhi; Wang, Qianqiu; Wu, Minzhi (Frontiers in Medicine, 2022)
Objectives: To define the clinical features of ocular syphilis and analyze the cerebrospinal fluid (CSF) of ocular syphilis patients to determine the co-occurrence of neurosyphilis. Methods: This was a retrospective study of 17 patients (23 eyes) with ocular syphilis admitted to the Fifth People’s Hospital, Suzhou, China from September 2017 to December 2021. Clinical manifestations, laboratory tests, treatment, and clinical outcomes were analyzed, and a review was conducted. Results: Eight males (12 eyes) and nine females (11 eyes) were enrolled. Mean patient age was 49.06 ± 3.47 years. The total manifestation time for ocular symptoms ranged from 10 days to 6 years. The cohort was comprised of three cases of early syphilis, four cases of late syphilis, and ten cases of unknown stage. The primary complaints were decreased visual acuity in 15 cases (21 eyes), ptosis in 1 case (1 eye), and loss of light perception in 1 case (1 eye). Cases were diagnosed as chorioretinitis in 7 cases (8 eyes), optic nerve retinitis in 4 cases (6 eyes), optic neuritis in 4 cases (7 eyes), and oculomotor nerve palsy in 1 case (1 eye)，syphilitic stromal keratitis in 1 case (1 eye). Serum HIV antibody was positive in one case（Nos.2）. All patients had reactive serum Treponema Pallidum Particle Agglutination (TPPA) and Toluidine Red Unheated Serum Test (TRUST). All patients underwent CSF examination. CSF white blood cell count was ≥5 × 106/L in 13 cases, CSF protein was >500 mg/L in 6 cases, TPPA was reactive in 15 cases, and TRUST was reactive in 5 cases. Eleven cases were also diagnosed with neurosyphilis. Patients were treated with either penicillin G sodium or ceftriaxone sodium. At time of discharge, 12 patients reported improved visual acuity. Abnormal serum or CSF examination improved in ten patients during the 6–12 month follow-up. Conclusion: Visual acuity loss is a warning indicator of ocular syphilis. Ocular syphilis primarily manifests as posterior uveitis, involving the choroid, retina, and optic nerve, and often co-occurs with neurosyphilis. Effective treatment should be administered immediately to avoid irreversible visual impairment and other serious adverse outcomes.